AS MUITAS FACETAS DE UM DIÁRIO: UMA LEITURA POLÍTICA DE UM FALCÃO NO PUNHO DE MARIA GABRIELA LLANSOL - KRAMER, VANESSA APARECIDA (2017)
The aim of this paper is to analyze the work Um Falcão no Punho: diário I written by the Portuguese writer Maria Gabriela Llansol under the perspective of The Political Unconscious (1992) by Frederic Jameson and Duas Meninas (1997) by Roberto Schwarz. The text underwent a political reading taking into account the ‘concentric circle’ proposed by Jameson, which, as well as the one introduced by Schwarz, in three interpretative levelswhichwidenin each layer, in order to expand the semantic horizon of the text. In the first level, we approach the text as a symbolic act, in which we limit ourselves to the ideal moment of the literary creation, which is, the daily narration of Llansol. In the second level, we approach the great discourses of the story, which are presented as a rewritten in the narrative and remain open, in a conflicting class struggle, which corresponds to the dictatorial political system of Portugal in the 20th century. In the third level, we reach the ideology of form that leads us to the matter of how the writer chose to narrate her memories: the diary. When we read considering the three levels, we unveil the strategies of containment used by the writer to soften the central theme of her book - Salazar’s dictatorship, as well as the impacts that this power generated in the geopolitical context of Portugal in that period – content repressed in the text by the narrative engendering, in an ingenious and intricate language of meanings that are veiled in a self-writing, which apparently is an ordered whole, but, when analyzed, it reveals conflicting elements. Having that objective, we first discuss about the basis of the memorialistic genre, especially the diary, with the authors' considerations that deal with intimate writing. Then, we introduced the historical context that permeated the literary production, as well as the critical fortune of Llansol. Furthermore, we approach the theoretical background that conducts this analysis, which proposes to think the literature associated with social issues and, finally, we perform the analysis of Um Falcão no Punho as a unique and particular mediation in the historical context to which it was imagined.